Comparison of continuous versus interrupted method of abdominal fascia closure using non - absorbable suture in the patients of acute peritonitis: our experience of 60 cases - Kumar, Basudev; Jauhari, Abhinav (International Journal of Research in Medical Sciences, 2017)
Background: The best method of wound closure would be one that provides adequate tensile strength to the incision until the wound heals and approximates the tissue in a way that normal healing mechanism can occur under optimal circumstance. The suture should remain secure even in the presence of local or systemic infection. The continuous suture has the advantage of an evenly distributed tension across the suture line and being more expedient. It also has the advantage of having a single suture line holding the fascia together. The interrupted suturing technique has the disadvantage of being time consuming. Methods: All the patients of peritonitis were taken up for emergency laparotomy fulfilling the inclusion criteria will be included in the study. They were divided into two groups A and B by randomization technique. Each group contained 30 patients each. Patients included in group A underwent continuous method of abdominal fascia closure post laparotomy. Patients included in group B underwent interrupted method of abdominal fascia closure post laparotomy. Results: In the present study, 60 cases of peritonitis were taken up, out of these mean age in the two groups were 34.03 years and 35.03 years respectively, majority of the patients were male 50 (83.3%); Most common diagnosis was of duodenal perforation peritonitis with 22 patient (36.7%), with Ileal perforation peritonitis 15 patients (25.0%), Kochs perforation peritonitis 13 patient (21.7%); Mean time taken for closure in continuous group was 13.10 minutes as compared to 16.00 minutes in interrupted group, This difference was statistically significant. Wound infection rate in two group were 26.7% and 33.3% respectively, wound infection was present in 30%of total patient. Burst abdomen was present in 20% in both the group. Conclusions: Continuous suturing with polypropylene is comparable to interrupted suturing in terms of wound infection, frequency of burst abdomen. Although continuous suturing is better than interrupted suturing as it is faster, take less time in closure than interrupted closure. Continuous polypropylene thus becomes the preferred material and method of closure for abdominal fascia for acute peritonitis.